Click‐to‐Release from trans‐Cyclooctenes: Mechanistic Insights and Expansion of Scope from Established Carbamate to Remarkable Ether Cleavage. Issue 33 (27th June 2018) - Versteegen, Ron M.; ten Hoeve, Wolter; Rossin, Raffaella; de Geus, Mark A. R.; Janssen, Henk M.; Robillard, Marc S.
Abstract: The bioorthogonal cleavage of allylic carbamates from trans ‐cyclooctene (TCO) upon reaction with tetrazine is widely used to release amines. We disclose herein that this reaction can also cleave TCO esters, carbonates, and surprisingly, ethers. Mechanistic studies demonstrated that the elimination is mainly governed by the formation of the rapidly eliminating 1, 4‐dihydropyridazine tautomer, and less by the nature of the leaving group. In contrast to the widely used p ‐aminobenzyloxy linker, which affords cleavage of aromatic but not of aliphatic ethers, the aromatic, benzylic, and aliphatic TCO ethers were cleaved as efficiently as the carbamate, carbonate, and esters. Bioorthogonal ether release was demonstrated by the rapid uncaging of TCO‐masked tyrosine in serum, followed by oxidation by tyrosinase. Finally, tyrosine uncaging was used to chemically control cell growth in tyrosine‐free medium. Abstract : Click‐to‐release… more : In addition to cleaving carbamates, the inverse‐electron‐demand Diels–Alder pyridazine elimination reaction can, with the same efficiency, cleave aromatic, benzylic, and even aliphatic ethers, as well as esters and carbonates. trans ‐Cyclooctene‐caged tyrosine was rapidly uncaged by treatment with tetrazine and subsequently oxidized by tyrosinase, whereas the caged tyrosine itself was not a substrate.